Photosynthetic activities of oil palm and its understory cover crops under shade - Jumena Adijaya; Herdhata Agusta; Sudrajat Sudrajat; Supiandi Sabiham; Triadiati Triadiati (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2026)
Photosynthesis is a key part of how oil palm ecosystems store carbon. The net CO₂ assimilation rate is greatly affected by the concentration of CO₂ between cells (Ci). Nonetheless, data on the assimilation–intercellular CO₂ (A/Ci) response of oil palm and understory vegetation in shaded mineral soil conditions remain inadequate. This study aimed to assess the A/Ci response characteristics and essential photosynthetic variables of oil palm (Elaeis guineensis Jacq.) and two understory cover crops, Asystasia gangetica and Nephrolepis biserrata, cultivated beneath mature oil palm canopies. The study was conducted at the Cikabayan Teaching Farm, IPB University, Bogor, Indonesia. A portable photosynthesis system was used to measure gas exchange variables at different times of the day. These included net CO₂ assimilation rate (A), stomatal conductance, transpiration rate, and intercellular CO₂ concentration (Ci). The results indicated clear physiological differences in the responses of canopy and understory vegetation. The Ci values of oil palm remained fairly stable throughout the observation period. On the other hand, understory species showed greater changes, requiring more Ci in the morning and less in the afternoon. Nephrolepis biserrata exhibited higher net assimilation than A. gangetica, indicating greater photosynthetic efficacy in shaded environments. These findings underscore the divergent photosynthetic regulation between canopy and understory vegetation, underscoring the significance of understory plants in facilitating carbon assimilation dynamics in shaded oil palm ecosystems. Keywords: absorption of CO2; Asystasia gangetica; Nephrolepis biserrata; stomatal conductances